Tianeptine esters derivatives : a study of protein-drug interaction performed by fluorescence quenching and molecular docking - Soares, Franciela Arenhart (2019)
The nature of binding between bovine serum albumin (BSA) and the antidepressant tianeptine and a new series of esters derivatives were studied in this paper. The interactions with BSA were investigated by UV-Vis and fluorescence spectroscopy at three different temperatures. The fluorescence quenching experiments showed that BSA interactions with tianeptine could be dynamic while to its esters a static mechanism was observed. The results showed that tianeptine quenches the intrinsic fluorescence of BSA more efficiently than its esters due to the presence of the free acid portion. The number of binding sites determined by fluorescence spectroscopy is approximately equal to 1 indicating that there is one binding site between BSA tianeptine esters, but the presence of a second interaction site for tianeptine at higher temperatures could be not ruled out. Molecular docking calculations point out a strong affinity of tianeptine and its esters to the site IIA of protein, supporting the hypothesis of a static quenching mechanism.